On Testing Theories of Financial Intermediary Portfolio Selection - Berndt, E. R.; McCurdy, T. H.; Rose, D. E. (Review of Economic Studies, 1980)
Ernst R. Berndt, Thomas H. McCurdy, David E. Rose; On Testing Theories of Financial Intermediary Portfolio Selection, The Review of Economic Studies, Volum